Detail Sedimentological Logging of Miri Hospital Road Outcrop, the Miri Formation, Sarawak - Sapari, Nasiman (2008)
The Miri Formation is a siliciclastic sequence consists of a succession of coarsening upwards clay-sand packages that is restricted to the coastal area between Miri and Jerudong but the main outcrops of this formation are in Miri, northeast Sarawak. There are at least nine best outcrops to be studied in Miri town. The most interesting is a Miri Hospital Road outcrop show a thick vertically dipping layer and sub-horizontal or gently dipping sequence are adjacent to each other. This outcrop remains a challenge because the correlation between these vertical and sub-horizontal dipping layers is still questionable today. One of the methods applied then by making detail field sedimentological logging of this outcrop in 1 cm: 100 cm scale with sampling of the different types of Miri sandstones. The investigated sedimentary sections in this area were aligned in southeastern direction with total 404 meters thick vertically. Fifteen facies were recognized based on lithology, sedimentary structures and fossil traces bed geometry. These are; i) facies A - trough cross-stratified sandstone with mud drapes; ii) facies B - parallel stratified sandstone with mud drapes; iii) facies C - wavy-bedded sandstone; iv) facies D - rhytmic stratified sandstone and mudstone; v) facies E - lenticular bedding; vi) facies F - homogenous coarse grained sandstone; vii) facies G - swaley cross-stratified sandstone; viii) facies H - thick amalgamated hummocky cross-stratified sandstone; ix) facies I - fine-grained bioturbated sandstone; x) facies J - interbedded to bioturbated siltstone and fine sandstone; xi) facies K - bioturbated siltstone; xii) facies L - mudstone inter-bedding with parallel stratified to hummocky cross-stratified sandstone; xiii) facies M - sand-clay alternation facies; xiv) facies N – massive coarse sandstone with liesegang; xv) facies O – flasser-bedded sandstone; xvi) facies P – thick, massive and structureless sandstone.; xvii) facies Q – sandstone and shale interbedding with the presence of the sedimentary dike; xviii) facies R – graded siltstone. Overall the outcrop consists of well defined beds of shale and sandstone in the lower part and become more arenaceous to the upper where shale-sandstone alternations are more numerous and irregular and the sandstone beds merge gradually into clayey sandstone and sandy or silty shale. The depositional environment interpretation of this area is inter-tidal flat environment particularly in muddy-sandy and mixed parts tidal setting where represent deposits of current ripples.